Efforts to Improve the Quality of Palm Kernel Cake through Fermentation Technology and Enzyme Addition for Poultry - Tiurma Pasaribu (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Palm kernel cake (PKC) with the protein content 14-21% and crude fiber about 17.63% is a by product of palm kernel oil. Utilization of PKC as source of protein for poultry feed is still limited. While demand of feed is getting increased. Therefore, the technology to improve PKC quality is needed to optimalize using PKC. This paper inform any efforts to improve the quality of PKC through fermentation technology and addition of enzymes and their utilization as poultry feed ingredient. Fermentation process of PKC can be done using single bacteria, mold or combination of them. By fermentation technology, the protein of PKC increased up to 88% (from 13-15% to 16-28%) and crude fiber decreased by 28% (from 17 to 12.21%). Palm kernel cake after fermentation can substitute soybean meal up to 18%, can be used up to 21% in broiler ration, and up to 25% in layer ration. Enzyme addition could increase metabolisable energy. Fermented PKC and enzyme addition can improve feed efficiency and feed conversion, and reduce abdominal fat in the broiler. Fermentation technology and addition of enzyme to PKC could improve the nutritional quality of PKC.